PENGARUH PAJAK PENGHASILAN, CASH HOLDING DAN RISIKO KEUANGAN TERHADAP INCOME SMOOTHING - Setyaningsih, Ayu; Irawati, Wiwit (Lembaga Penerbitan Unversitas Esa Unggul, 2024)
This study tries to analyze the effect of income tax, cash holding and financial risk on income smoothing. This study uses secondary data. This type of research is a quantitative approach research with a descriptive analysis method. Samples were taken using a purposive sampling technique. The sample consists of 66 data from 11 companies in the property and real estate sector listed on the Indonesia Stock Exchange in 2017-2022. The data analysis technique used in descriptive statistical technique and panel data regression using Eviews 12. Based on the results of this study, it shows that Income tax, cash holding and financial risk have a simultaneous effect on income smoothing. Partially, cash holding has an effect on income smoothing, while income tax and financial risk have no effect on income smoothing.